Factors Influencing Life Satisfaction in Basic Education Teachers - de Souza, Luciana Karine; Martínez, Sophia Beylouni Santos; Gauer, Gustavo; Bataglia, Patrícia Unger Raphael [UNESP]; Hutz, Claudio Simon (FapUNIFESP (SciELO), 2023)
This study explored how the following aspects may influence basic education teachers’ life satisfaction: self-esteem, general self-efficacy, self-compassion, positive and negative feelings, moral competence, social support, positive relationships with a colleague, work engagement, age, professional experience (in years), time teaching in the same school, number of schools currently teaching, and approximate number of students per week. One hundred primary and high-school teachers (74 women) participated in the study (mean age 40.9; SD = 10.01). Network analysis provided a model which encompasses the six most relevant aspects that interfere in the life and work of basic education teachers: life satisfaction, self-efficacy, self-esteem, positive affects, work engagement, and giving instrumental social support. In addition, the yielded model showed that self-efficacy presented the closest relationship with life satisfaction. We discuss the results in line with previous studies on self-efficacy. Interventions directed at basic education teachers may be more effective if self-efficacy is part of the program.
Factores que Influyen en la Satisfacción de Vida en Docentes de Educación Básica
Fatores que Influenciam a Satisfação de Vida em Professores da Educação Básica
Keywords: autoeficacia; autoeficácia; calidad de vida; profesores; professores; qualidade de vida; quality of life; self-efficacy; teachers